Honeycomb porous MnO2 nanofibers assembled from radially grown nanosheets for aqueous supercapacitors with high working voltage and energy density - Zhao, Lei; Yu, Jie; Li, Wenjun; Wang, Shuguang; Dai, Chenglong; Wu, Junwei; Bai, Xuedong; Zhi, Chunyi (Nano energy, 2014)
Honeycomb porous MnO2 nanofibers (HMONFs) have been prepared by solution reaction between KMnO4 and electrospun carbon nanofibers (CNFs). The HMONFs are entirely composed of radially grown MnO2 nanosheets with thickness about 3–7nm, which interconnect each other, forming the honeycomb pores. Formation of this unique structure occurs only at very low KMnO4 concentrations and sufficiently long reaction time. The constituting MnO2 nanosheets in the HMONFs are well separated with the sheet edges oriented on the surface, leading to excellent supercapacitive performance. Symmetric aqueous supercapacitors are assembled using the HMONFs and 1M Na2SO4 electrolyte, which exhibits a working voltage as high as 2.2V and high energy density of 41.1Wh/kg at the power density of 3.3kW/kg. The supercapacitor capacity can be retained about 76% of its initial value after 3500 cycles, which is acceptable due to its high energy density. These results indicate that the HMONFs are of high promise in developing advanced supercapacitors with high working voltage and energy density for practical applications. [Display omitted] •Honeycomb porous MnO2 nanofibers (HMONFs) were prepared.•The HMONFs were entirely composed of radially grown MnO2 nanosheets.•The HMONFs exhibit excellent supercapacitor performance in aqueous electrolyte with high working voltage (2.2V) and energy density (41.1Wh/kg at 3.3kW/kg).